Russian foreign policy interests, vectors, and sectors - Gvosdev, Nikolas K. (SAGE, 2014)
Gvosdev and Marsh's text covers not only contemporary Russian policies towards the various regions of the world, but also looks at the interactions between the various constituencies that shape and influence Russian foreign policy.